Effet de l’irradiation UV sur les spores d’Aspergillus sp. et sélection de certaines mutations - KHODJA, SAMIRA (My University, 2025)
Fungi of the Aspergillus genus play a major role in scientific research due to their biotechnological applications and their ability to resist environmental stress. This study aimed to evaluate the effect of ultraviolet-C (UVC) radiation (254 nm) on the viability of Aspergillus sp. spores, and to assess the impact of a fungicide on their growth and sporulation. The fungal strain was isolated from moldy bread, cultured on PDA medium, and exposed to various durations of UVC radiation. Serial dilutions and inoculations were carried out under sterile conditions. In parallel, different concentrations of a fungicide were applied to compare its effect with that of the UV treatment. Results showed a gradual reduction in spore viability with increasing UVC exposure time, leading to total lethality after 16 minutes. Some colonies from intermediate exposures exhibited morphological changes suggestive of mutations. In contrast, the tested fungicide did not inhibit fungal growth, but reduced sporulation. These findings confirm the mutagenic potential of UVC radiation and highlight the possible resistance of Aspergillus sp. to fungicidal treatment. This study opens up new perspectives for selecting mutant strains and evaluating antifungal resistance.
Keywords: Aspergillus sp., UVC radiation, spores, mutations, fungicide, viability